1988
DOI: 10.1002/ijc.2910420509
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of HTLV‐i in gabon (western equatorial Africa)

Abstract: In 1986 a survey to determine the distribution of HTLV-I infection was conducted in Gabon in a representative sample of adults and children. Five samples were taken in adults and 2 samples in children living in urban and rural areas. Samples were taken by the cluster sampling technique, i.e., clusters of randomly selected households. Sera were tested for IgG antibodies to HTLV-I by ELISA. ELISA-positive sera were retested by Western blot. The study comprised 1,874 adults and 684 children, all apparently health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…Using strict Western blot serological criteria, as well as specific molecular detection, we found an HTLV-1 prevalence of 5% in the Haut Ougoué region, compared with 0 to 2.1% in the four other provinces. A study published in 1988 indicated that HTLV-1 infection is endemic in Gabon, with an overall higher seroprevalence in adults (5 to 10% according to area) than in children (7). Furthermore, the prevalence of HTLV-1 infection in pregnant woman was reported previously to be 6.8 to 10% (51) on the basis of one epidemiological study performed in one region of the country (southeast).…”
Section: Discussionmentioning
confidence: 97%
“…Using strict Western blot serological criteria, as well as specific molecular detection, we found an HTLV-1 prevalence of 5% in the Haut Ougoué region, compared with 0 to 2.1% in the four other provinces. A study published in 1988 indicated that HTLV-1 infection is endemic in Gabon, with an overall higher seroprevalence in adults (5 to 10% according to area) than in children (7). Furthermore, the prevalence of HTLV-1 infection in pregnant woman was reported previously to be 6.8 to 10% (51) on the basis of one epidemiological study performed in one region of the country (southeast).…”
Section: Discussionmentioning
confidence: 97%
“…The virus is endemic in southwestern Japan [66], Africa [67,68], the Caribbean Islands [69] and South America [70] and is frequently found in Melanesia, Papua New Guinea [71], Solomon Islands and Australian aborigines [62]. HTLV-1 also is prevalent in certain populations in the Middle East [72] and India [73,74].…”
Section: Epidemiologymentioning
confidence: 99%
“…11 Some strains belonged to the B subtype with isolates from Congo, Cameroon, and Central African Republic, 12 whereas others belonged to the widely dispersed A subtype.…”
Section: Introductionmentioning
confidence: 98%